Measuring Personal Cultural Orientations: Scale Development and Validation - Sharma, Piyush (Sage Publications, 2010)
Cross-cultural studies using Hofstede’s national scores to operationalize his five cultural factors at an individual level suffer from ecological fallacy, and those using self-report scales treat cultural factors as unidimensional constructs and provide little or no evidence of the construct validity and measurement equivalence of these scales. This paper reconceptualizes Hofstede’s five cultural factors as ten personal cultural orientations and develops a new 40-item scale to measure them. It also establishes the validity, reliability, and cross-cultural measurement equivalence of the new scale, and discusses its advantages over other scales.